بناء قائمة مرجعية مقترحة لتقويم كتب مقررة في اللغة العربية لأغراض علمية =Towards developing an evaluation checklist proposed for textbook in Arabic for academic purposes - Haji Daud, Nadwah; Omar, Ummi Farhanah; Sahrir, Muhammad Sabri (Department of Arabic And Middle Eastern languages, Faculty Of Languages And Linguistics. University of Malaya, 2016)
The teaching language for specific purposes is a field with an intervention of continuous developments that are consistent with the needs of the learner, which are moving with developments in the field of specialty. This condition requires the textbooks used in the field to be in pace with the modern changes in field of specialization. Among the best ways to determine this is by evaluating the textbook in several aspects and criterion. Although there have been many evaluation instruments, the textbook evaluation is a subjective process in which it has no specific checklist consisting of standard evaluation that can be applied to all educational contexts in order to conform to the learning culture and environment. Hence, this study aims to develop a new checklist of items in order to evaluate the textbook of Arabic Language for Academic Purposes among learners at the International Islamic University in Malaysia. This study will present a range of checklist items used in language for specific purposes textbook evaluation in general. These items, then, are discussed and analyzed in terms of structures and practicality to the current educational environment based on the results of previous studies in this field. By then, the selection of appropriate items to evaluate the textbook for academic purposes is done.